Impedance Spectroscopy of Nanostructure p-ZnGa2Se4/n-Si Heterojunction Diode - Yahia, I. S.; Fadel, M.; Sakr, G. B.; Shenouda, S. S.; Yakuphanoğlu, Fahrettin; Farooq, W. A. (Polish Acad Sciences Inst Physics, 2011)
The impedance characteristics of the nanostructure p-ZnGa2Se4/n-Si heterojunction diode were investigated by impedance spectroscopy method in the temperature range (303-503 K) and the frequency range (42 Hz - 5 MHz). The real and imaginary parts of the complex impedance are changed with the frequency. Both are decreased with increasing temperature at the lower frequencies and are merged at the higher frequencies. The dielectrical relaxation mechanism of the diode was analyzed by the Cole-Cole plots. The Cole-Cole plots under various temperatures exhibit one relaxation mechanism. With increasing temperature, the radius of the Cole-Cole plots decreases, which suggests a mechanism of temperature-dependent on relaxation.
Keywords: Nonlinear-Optical Properties; Electrical-Properties; Defect-Chalcopyrite; Thin-Films